Experimental study on the dynamic behavior of T-shaped steel reinforced concrete columns under impact loading. (1st April 2020) - Xiang, Sheng; Zeng, Lei; Liu, Yanhua; Mo, Jinxu; Ma, Linling; Zhang, Jicheng; Chen, Juan
Highlights: Seven steel reinforced columns are tested under impact loading. Lower stirrup spacing can improve impact resistance of columns. Finite element models are developed to simulate the experiments. Predicated results have good agreement with test results. Abstract: This paper reports an experimental investigation into the behavior of axially loaded steel reinforced concrete (SRC) columns subjected to impact loads. A total of seven SRC columns with T-shaped steel skeleton were prepared and tested using a drop hammer impact system. The testing variables include the impact height, stirrup spacing and the axial compression ratio. The impact force time histories and lateral displacements at mid-span and quarter-span were recorded and analyzed. The experimental results indicated that the decrease of stirrup spacing resulted in a smaller lateral deflection. Axial load was also found to have a strong influence on the residual deflection of columns subjected to impact loading. In addition, the finite element analysis models, which considers the effects of strain rate of steel and concrete as well as the axial loads, were established to simulate the experiment. The FEA results are proved to agree well with that of experiment. The findings obtained from this study can facilitate the application of SRC columns in improving the impact-resistant performance of bridge and building columns.